2015
DOI: 10.1038/srep15512
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolomics reveals metabolic changes in male reproductive cells exposed to thirdhand smoke

Abstract: Thirdhand smoke (THS) is a new term for the toxins in cigarette smoke that linger in the environment long after the cigarettes are extinguished. The effects of THS exposure on male reproduction have not yet been studied. In this study, metabolic changes in male germ cell lines (GC-2 and TM-4) were analyzed after THS treatment for 24 h. THS-loaded chromatography paper samples were generated in a laboratory chamber system and extracted in DMEM. At a paper: DMEM ratio of 50 μg/ml, cell viability in both cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…GSH is a major component of the antioxidant defense pathway and these findings suggest spermatogonia might use this enzyme to combat the high levels of oxidative stress [18]. In TM-4 cells, there are increased metabolites involved in nucleic acid metabolism, suggesting that THS toxins are genotoxic and have the ability to compromise the integrity of genetic material [18]. THS exposure did not have effects on cell viability, cell cycle or apoptosis in these two male germ cell lines [18].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…GSH is a major component of the antioxidant defense pathway and these findings suggest spermatogonia might use this enzyme to combat the high levels of oxidative stress [18]. In TM-4 cells, there are increased metabolites involved in nucleic acid metabolism, suggesting that THS toxins are genotoxic and have the ability to compromise the integrity of genetic material [18]. THS exposure did not have effects on cell viability, cell cycle or apoptosis in these two male germ cell lines [18].…”
Section: Introductionmentioning
confidence: 94%
“…It also has been shown that THS toxins have the ability to cause metabolic changes in two male germ cell lines [18]. When spermatogonia (GC-2) and sertoli derived cells (TM-4) were exposed to THS toxins for 24 hours, the investigators observed changes in metabolic enzymes involved in glutathione, ammonia and nucleic acid metabolism [18]. In GC-2 cells, THS exposure resulted in increase in synthesis and decrease in the breakdown of GSH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…THS cytotoxicity was verified by altered mitochondrial function in mNSC, but the potential for damage decreased as the sample aged 62,75,76 . There was even a decrease in the total number of cells, caused by inhibition of cell proliferation.…”
Section: Effects Of Ths On Healthmentioning
confidence: 99%
“…Even at concentrations incapable of causing cytotoxic effects, two murine male reproductive cell lines (GC-2 and TM-4), when exposed to THS, presented altered metabolite levels and gene expression of enzymes related to metabolism and oxidative stress 76 . The study warned of THS action on systems that are not the prime target of cigarette smoke, but which can have their function compromised by continuous exposure.…”
Section: Effects Of Ths On Healthmentioning
confidence: 99%